Neonatal leishmaniasis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2010)
Cutaneous leishmaniasis in Italy is caused by Leishmania tropica. In Apulian region about ten cases a year were observed in the past, mainly coming from the coast villages of Matera and Cosenza provinces. Nowaday, their number is significantly decreased, whereas dog leishmaniasis is very frequent. Although the child can be affected by leishamaniasis in the first year of life, neonatal leishmaniasis is exceptional (1). The face is the site most frequently involved in the child (2). The case here reported was exceptional for its very early onset, which did not suggest initially the diagnosis of leishmaniasis, and also for the lack of spontaneous regression after 17 months, that led us to perform intralesional therapy with glucantim®.